2013
DOI: 10.1111/ajt.12470
|View full text |Cite
|
Sign up to set email alerts
|

Results of Implementation of Preventive Recommendations for Tuberculosis After Renal Transplantation in an Endemic Area

Abstract: This retrospective cohort study assessed the results of the implementation of preventive recommendations for tuberculosis (TB) among renal transplant recipients in an endemic area (Rio de Janeiro, Brazil). Subjects were defined as at high risk for TB if they had latent tuberculosis infection (LTBI), reported recent close contact with individuals with TB or received a graft from a donor with LTBI. A 6-month course of isoniazid preventive therapy (IPT) was targeted to high-risk subjects. The study end point was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 23 publications
1
33
0
4
Order By: Relevance
“…As reported by others, the use of "universal" isoniazid prophylaxis in living-related kidney transplantation in an endemic area resulted in reduced numbers of active tuberculosis after transplantation. [20][21][22] WHO estimates the incidence rates of tuberculosis in Saudi Arabia to be 14 per 100 000 in 2013 (range, 12-16 per 100 000). 13 The prevalence of LTBI (defined as TST reaction of ≥10 mm) in the general population was reported in a nationwide survey in 1993 to be 33% in people without prior BCG vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by others, the use of "universal" isoniazid prophylaxis in living-related kidney transplantation in an endemic area resulted in reduced numbers of active tuberculosis after transplantation. [20][21][22] WHO estimates the incidence rates of tuberculosis in Saudi Arabia to be 14 per 100 000 in 2013 (range, 12-16 per 100 000). 13 The prevalence of LTBI (defined as TST reaction of ≥10 mm) in the general population was reported in a nationwide survey in 1993 to be 33% in people without prior BCG vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…We have read with interest the article by de Lemos et al (1) regarding the implementation of a preventive protocol for latent tuberculosis infection (LTBI) in kidney transplant recipients residing in Brazil. In that study, all recipients and living donors were intended to be screened preoperatively or at the time of transplantation for epidemiological, clinical and radiological evidence of LTBI.…”
Section: To the Editormentioning
confidence: 99%
“…Our extensive review of the literature identified four other detailed case reports that documented the development of active TB disease after LTBI treatment . In addition, we found a total of 56/2651 (2.1%) cases of active TB among 41 observational cohorts and six RCT . Among them, only five cases were described in detail.…”
Section: Resultsmentioning
confidence: 95%
“…We found 41 cohort studies that evaluated the outcome of LTBI therapy. Eleven were from Europe, 10 from US and Asia, seven from South America, and one each from Africa, Australia, and Canada . Only nine were prospective .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation